Therapeutic behavior in elderly with Parkinson disease - Rita Mesa Valiente; Yanay Pérez Pérez; Lucía Nivia Turro Mesa; Eloy Turro Caró (Centro Provincial de Información de Ciencias Médicas, 2018)
Parkinson disease is a degenerative process of the central nervous system of progressive insidious beginning and slow development which is the consequence of an idiopathic lesion in the extrapiramidal system and which clinical manifestations are rigidity, tremor and bradykinesia. It is presented in people of advanced age, without differences as for sex, race or social-economic class, and its definitive diagnosis is determined through the clinical method. In this respect, the therapeutic approach that should be followed in the elderly that suffers the disease is described in this work, in which the non pharmacological treatment should be focused to improve the patient and family physical and psychical situation, according to the evolutive course, and the pharmacological treatment is based on levodopa as election drug, with which it is possible to elevate the life quality of the affected patients.